2020
DOI: 10.1038/s41598-020-62981-1
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Course of Acute Kidney Disease after Cardiac Surgery: A Retrospective Observational Study

Abstract: Acute kidney disease (AKD), or renal dysfunction persisting >7 days after an initiating event of acute kidney injury, is a rising concern. This study aimed to elucidate the clinical course of AKD after cardiac surgery with data on post-cardiac surgery patients admitted to intensive care units (ICU) at 18 Japanese hospitals during 2012-2014. Using multivariable logistic models, we evaluated the association of AKD with 90-day mortality and the 50% eGFR decline during 2-year follow-up compared to eGFR at 90 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
52
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 31 publications
8
52
1
Order By: Relevance
“…16 , 33 Patients with AKI that evolves into acute kidney disease show greater long-term eGFR decreases than patients with AKI who do not develop acute kidney disease. 34 Older age, male sex, Black race, underlying CKD, and AKI severity are known risk factors for AKI progression to acute kidney disease 35 , 36 ; however, the accelerated eGFR decrease following COVID-19–associated AKI persisted after adjusting for these covariates. As in acute tubular necrosis, where patients with acute tubular necrosis due to mixed causes are at higher risk for future CKD than patients with acute tubular necrosis due to a single cause, such as ischemia or nephrotoxins, 37 the multiple concurrent mechanisms of COVID-19–associated AKI may be contributing to the increased eGFR decrease after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…16 , 33 Patients with AKI that evolves into acute kidney disease show greater long-term eGFR decreases than patients with AKI who do not develop acute kidney disease. 34 Older age, male sex, Black race, underlying CKD, and AKI severity are known risk factors for AKI progression to acute kidney disease 35 , 36 ; however, the accelerated eGFR decrease following COVID-19–associated AKI persisted after adjusting for these covariates. As in acute tubular necrosis, where patients with acute tubular necrosis due to mixed causes are at higher risk for future CKD than patients with acute tubular necrosis due to a single cause, such as ischemia or nephrotoxins, 37 the multiple concurrent mechanisms of COVID-19–associated AKI may be contributing to the increased eGFR decrease after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Again, this reflects the real world setting. Fifth, due to low numbers of patients, our renal recovery analysis is hypothesis generating and we were unable to look at incidence of acute kidney disease (AKD), an important interim diagnosis, with increasingly recognised implications for long-term kidney function 45 . However, we note that the specific criteria for AKD have not been agreed 13 .…”
Section: Discussionmentioning
confidence: 99%
“…AKI and AKD reflect renal function status in different time periods during the disease process. Although studies have shown that AKD is associated with increased risks of mortality and renal function decline after hospital discharge ( Hsu et al, 2020 ; James et al, 2019 ; Kofman et al, 2019 ; Matsuura et al, 2020 ; Mizuguchi et al, 2018 ), few targeted on patients with AKD after AKI, and the epidemiology of hospitalized patients with AKD after AKI is largely unknown. Whether AKD acts as an important intermediate stage for progression to renal dysfunction, chronic dialysis and mortality after AKI remains to be found.…”
Section: Introductionmentioning
confidence: 99%